BACTERIAL ISOLATES FROM AQUARICULTURE SYSTEMS: IDENTIFICATION BY 16SRDNA AMPLIFICATION AND SEQUENCE ANALYSIS - P. SEETHALA DEVI; A. UMA; G. REBECCA (International Journal of Pharma and Bio Sciences, 2013)
Aquariculture is the farming of ornamental animals and plants. As bacterial diseases cause major production and economic losses in ornamental fish culture, early identification of bacterial pathogens from such systems would help to take suitable management measures to avoid huge losses. Bacterial isolates from various aquariculture sytems were identified by PCR amplification of 16srDNA gene and nucleotide sequencing. This method is less time–consuming and more specific than conventional bacterial identification methods.